Increasing home dialysis knowledge through a web‐based e‐learning program. Issue 6 (June 2014) - Bennett, Paul N; Jaeschke, Sadie; Sinclair, Peter M; Kerr, Peter G; Holt, Steve; Schoch, Monica; Fortnum, Debbie; Ockerby, Cherene; Kent, Bridie
Abstract Aim There has been a global decline in the uptake of home‐based dialysis therapies in the past 20 years. The ability to provide appropriate information to potential patients in this area may be confounded by a lack of knowledge of home dialysis options. The aim of this study was to develop a web‐based education package for health professionals to increase knowledge and positive perceptions of home‐based dialysis options. Methods A three‐module e‐learning package concerning home dialysis was developed under the auspices of the home dialysis first project. These modules were tested on 88 undergraduate health professionals. Changes in attitudes and knowledge of home dialysis were measured using custom designed surveys administered electronically to students who completed the modules. Matched pre and post responses to the survey items were compared using Wilcoxon signed rank tests. Results The pre survey indicated clear deficits in existing knowledge of home dialysis options. In particular, when asked if haemodialysis could be performed at home, 22% of participants responded 'definitely no' and a further 24% responded 'probably no'. Upon completion of the e‐learning, post survey responses indicated statistically significant improvements (P < 0.001) in eight of the nine items. When asked if the e‐learning had increased their knowledge about home dialysis, 99% of participants responded 'definitely yes'. Conclusion A suite of web‐based education modules can successfully deliver significant improvements in awareness and knowledge around home dialysis therapies.